2018
DOI: 10.1111/1749-4877.12271
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary changes of Hox genes and relevant regulatory factors provide novel insights into mammalian morphological modifications

Abstract: The diversity of body plans of mammals accelerates the innovation of lifestyles and the extensive adaptation to different habitats, including terrestrial, aerial and aquatic habitats. However, the genetic basis of those phenotypic modifications, which have occurred during mammalian evolution, remains poorly explored. In the present study, we synthetically surveyed the evolutionary pattern of Hox clusters that played a powerful role in the morphogenesis along the head–tail axis of animal embryos and the main re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…These studies have been based on limited taxon sampling, including chondrichthyans, stem actinopterygians, squamates and crocodilians 1,[12][13][14] , and no study has examined axial complexity beyond Pan-Mammalia in a comprehensive phylogenetic framework including crown and stem taxa. Axial skeletal complexity is associated with numerous aspects of vertebrate biology, including regulatory genetic mechanisms, respiratory and locomotory function and ecology [1][2][3][4][5][6][7][8]12,13,15,16 . However, it is impossible to accurately associate these factors with morphological evolution without a quantified understanding of said morphology.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been based on limited taxon sampling, including chondrichthyans, stem actinopterygians, squamates and crocodilians 1,[12][13][14] , and no study has examined axial complexity beyond Pan-Mammalia in a comprehensive phylogenetic framework including crown and stem taxa. Axial skeletal complexity is associated with numerous aspects of vertebrate biology, including regulatory genetic mechanisms, respiratory and locomotory function and ecology [1][2][3][4][5][6][7][8]12,13,15,16 . However, it is impossible to accurately associate these factors with morphological evolution without a quantified understanding of said morphology.…”
Section: Main Textmentioning
confidence: 99%
“…
The axial skeleton is the central anatomical structure uniting vertebrates, varying across the clade in the total number of constituent elements and morphological complexity, associated with changes in regulatory genetic mechanisms, respiratory efficiency, and locomotory adaptation [1][2][3][4][5][6][7][8] . The evolution of this morphological complexity has historically been interpreted as a linear increase from relatively simple, homogeneous anatomies in tetrapods and stem mammals to uniquely high complexity in crown mammals 1,9-11 .
…”
mentioning
confidence: 99%
“…This suggests that HOXC10 might play a role in the development of pseudothumbs. In addition, pinnipeds and manatees (belonging to the family Trichechidae) underwent parallel evolution of HOXC10 (Li et al, 2018), which implies a potential important function. Furthermore, no direct studies have shown that HOXC10 interacts with PCNT or DYNC2H1, two genes that were identified as possibly related to pseudothumb development in a previous convergent evolution study of giant and red pandas (Hu et al, 2017).…”
Section: Foreground Branchmentioning
confidence: 99%
“…Genes belonging to the HOXA and HOXD families are important for the outgrowth and patterning of the limb (He, Nakada, & Morrison, 2009; Mallo, 2018). HOXB genes are involved in the differentiation of the hematopoietic progenitor cells, the homeotic transformation of the cervical vertebra, and defects in the closure of sternal rudiments in mice (Collins & Thompson, 2018; Li et al, 2018). The Deletion of HOXC genes results in lower extremity malformations (Alvarado, McCall, Hecht, Dobbs, & Gurnett, 2016).…”
Section: Introductionmentioning
confidence: 99%